Facilely prepared Fe3O4/nitrogen-doped graphene quantum dot hybrids as a robust nonenzymatic catalyst for visual discrimination of phenylenediamine isomers. Issue 20 (11th May 2016) - Shi, Bingfang; Su, Yubin; Zhang, Liangliang; Huang, Mengjiao; Li, Xuefeng; Zhao, Shulin
Abstract : A Fe3 O4 nanoparticle/nitrogen-doped graphene quantum dot hybrid was facilely prepared by a reducing agent-free strategy, and used for the visual discrimination of phenylenediamine isomers. Abstract : In this work, we report a reducing agent-free strategy for the synthesis of Fe3 O4 nanoparticle/nitrogen-doped graphene quantum dot (Fe3 O4 /N-GQD) hybrids, and constructed a sensing platform based on Fe3 O4 /N-GQDs for the visual discrimination of phenylenediamine isomers. Fe3 O4 /N-GQDs were facilely prepared by hydrothermal treatment of Fe 3+ /N-GQD solutions under alkaline conditions without other reagents. The prepared Fe3 O4 /N-GQDs exhibited outstanding peroxidase-like activity and were stable under a wide range of pH values and temperatures. The phenylenediamine isomers ( o -phenylenediamine, m -phenylenediamine, and p -phenylenediamine) were discriminated through the H2 O2 -mediated oxidation reaction using Fe3 O4 /N-GQDs as novel peroxidase mimics, which resulted in appreciable color changes. The proposed method is simple, economical, and effective for discrimination of isomers, and can be used for sensitive and selective quantitative analysis of o -phenylenediamine and p -phenylenediamine. A good linear relationship from 1 to 90 μM and a detection limit of 230 nM for o -phenylenediamine were achieved, and the linear relationship for p -phenylenediamine was from 2 to 70 μM with a detection limit of 530 nM. The proposed method may open new applications of Fe3 O4 /N-GQDs in biomedicine and environmental chemistry.